2019
DOI: 10.1017/s2045796019000118
|View full text |Cite
|
Sign up to set email alerts
|

Trends in pesticide suicide in South Korea, 1983–2014

Abstract: Aims Self-poisoning using pesticides is among the major methods of suicide worldwide, and accounts for one-fifth of suicides in 2006–2010 in South Korea. We investigated long-term trends in pesticide suicide rates in South Korea and factors related to these trends. Methods We calculated age-standardised rates of pesticide suicide in South Korea (1983–2014) using registered death data. We used graphical approach and joinpoint regression analysis to examine secular trends in pesticide suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
1
28
0
3
Order By: Relevance
“…Self-poisoning by highly toxic pesticides is a common suicidal method, so political intervention has been actively adopted in agricultural countries, including Sri Lanka and Bangladesh, and also in high-income countries, including the UK and South Korea [7,8,9,10,11,12]. South Korea introduced a complete ban on highly toxic pesticides in November 2012, and it effectively decreased both the suicide overall and suicide by pesticide rates [7,13,14,15]. The World Health Organization confirmed that South Korea made one of the most successful policies for suicide prevention [16].…”
Section: Introductionmentioning
confidence: 99%
“…Self-poisoning by highly toxic pesticides is a common suicidal method, so political intervention has been actively adopted in agricultural countries, including Sri Lanka and Bangladesh, and also in high-income countries, including the UK and South Korea [7,8,9,10,11,12]. South Korea introduced a complete ban on highly toxic pesticides in November 2012, and it effectively decreased both the suicide overall and suicide by pesticide rates [7,13,14,15]. The World Health Organization confirmed that South Korea made one of the most successful policies for suicide prevention [16].…”
Section: Introductionmentioning
confidence: 99%
“…At first, the present study confirms that the pesticide ban policy has had a good effect on suicide by pesticide in workers as in the general population. [7,[13][14][15] In a previous study, the age-standardized suicide by pesticide rate among the general population in South Korea went down from 2011 to 2013: 5.26 to 2.67 per 1,000,000; the complete regulation of highly toxic pesticides was introduced in 2012. [13,14] This reduction is significant in men, the elderly, and rural residents.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide by pesticide, which is preferred as a suicidal method in lower-class occupations, showed a positive association with the UnR, but the relationship disappeared in the third five-year period after the number had mainly decreased. [13,14] The CPI was calculated as the percentage of the rate from one year to another. The means of the CPI are 2.92, 2.98, and 1.24 for each five-year period analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive usage of pesticides (~ 1.4 million tons annually) has been reported in China [8] . Notably, suicide by pesticide poisoning is strongly associated with the proportion of the pesticide sold and management policies [9].The most common method of suicide in China was pesticide poisoning. Although the proportion of suicides using pesticides in China has decreased from approximately 62% [10] to 49% [11], self-poisoning with pesticides is still the leading cause of suicide.…”
Section: Introductionmentioning
confidence: 99%